COVID-19 associated meningoencephalitis or a neuropsychiatric manifestation of systemic lupus erythematosus-a diagnostic dilemma - Shrayhans, Sipani; Pooja, Khosla; Vinus, Taneja; Rishikesh, Dessai (International Journal of Research in Medical Sciences, 2023)
The infection with SARS-CoV-2 is associated with fever and respiratory symptoms but is not limited to respiratory system only. Since its appearance, several neurological symptoms have been reported, most commonly headache and anosmia, as well as less frequent complications such as COVID-19-associated encephalitis and meningitis. In this case report, we report a 40-year-old female recently infected with SARS-CoV-2, who presented with history of high-grade fever, cough, breathlessness 12 days back followed by altered sensorium and restlessness. The patient was also found to have underlying systemic lupus erythematosus which surfaced post-COVID-19 infection. Cerebrospinal fluid (CSF) analysis was done and the patient received IVIG therapy and showed dramatic improvement. SARS-CoV-2 has been implicated in development of autoimmune diseases.